A Close Look at Echium amoenum Processing, Neuroactive Components, and Effects on NeuropsychiatricÂ Disorders: - Araj-khodaei, Mostafa; Nouri, Mohammad; Farajdokht, Fereshteh; Torbati, Mohammadali; Ranjbar Kuchaksaray, Fatemeh; Hamedyazdan, Sanaz; Sadigh-Eteghad, Saeed (Galen Medical Journal, 2019)
Pharmacological researches in the area of herbal medicine have considerably increased over the last two centuries. Echium amoenum (known as Gol-e-Gavzaban in Persian) is a medicinal plant that has been widely used in Iranian folk medicine. In this review, databases including PubMed, Scopus, and Google Scholar were searched up. Data collecting was completed by January 2019 and available scientific reports regarding the processing methods, main chemical constituents, and effects of E. amoenum on different neuropsychiatric disorders are summarized. Thirteen five studies met the inclusion criteria. According to results, the important phytochemicals of the plant was phenolic compounds, fatty acids, rosmarinic acid, anthocyanidins, and flavonoids. Also, experimental and clinical studies demonstrated the effectiveness of E. amoenum in the treatment of several neuropsychiatric disorders such as anxiety, depression, ischemic stroke, seizure, Alzheimerâ€™s disease, and pain. Many of these effects are, at least in part, due to its rosmarinic acid or polyphenolic compounds such as flavonoids and natural pigments such as anthocyanins. Also, fatty acids such as gamma-linolenic acid play critical role in neuroactive properties of this herb. Among these effects, only the antidepressant and anxiolytic properties of the plant extract have been examined both experimentally and clinically. There was some controversy over its toxicity effects. It seems that E. amoenum protects neurons via attenuation of oxidative stress and inflammation as well as blocking of apoptosis in the nervous system. However, more studies are necessary for assessing exact mechanisms of action in neuropsychiatric disorders, finding of bioactive ingredients, and processing methods of this plant.Â [GMJ.2019;8:e1559]